Exploration of the mechanisms of change in constructs from self-determination theory and quality of life during a multidisciplinary family-based intervention for overweight adolescents - Fenner, A.; Howie, E.; Straker, Leon; Hagger, M. (Human Kinetics, 2016)
The current study explored whether a multidisciplinary family-based intervention underpinned by self-determination theory could enhance perceptions of parent need support, autonomous motivation, and quality of life in overweight and obese adolescents. Using a staggered-entry waitlist-period control design, adolescents (n = 56) were assessed at baseline and preintervention (within-participant control), immediately following intervention, and at 3, 6, and 12 month follow-ups. Parents were trained in need-supportive behaviors within the broader context of an 8-week multidisciplinary intervention attended jointly with adolescents. Following intervention, significant improvements were demonstrated in adolescent perceptions of parent need support, autonomous motivation, and quality of life, and changes were maintained at the 1-year follow-up. Mediation analyses revealed changes in perceptions of parent need support predicted changes in quality of life indirectly via changes in autonomous motivation. Findings suggest overweight and obese adolescents are likely to benefit from multidisciplinary family-based interventions that aim to train parents in need-supportive behaviors.